Use of virtual reality - Yip, Kah Yin (2018)
Virtual Reality (VR) and Augmented Reality (AR) are gaining attention in today’s world. Many companies like Apple and Google has developed their own AR app for developers to create VR or AR app and games. The project is to develop an AR app by making use of the available GPS information of manholes and routing information of the underground fiber network from Singtel. It will help engineers and field staffs to view and locate manholes across Singapore and provide them the routing information of pipes and cables laid underground when they are carrying out works on-site.